A Novel Three-Dimensional and Tissue Doppler Echocardiographic Index for Diagnosing and Prognosticating Heart Failure With Preserved Ejection Fraction - Wang, Weiding; Mu, Guanyu; Liu, Changle; Xie, Juan; Zhang, Hao; Zhang, Xiaowei; Che, Jingjin; Tse, Gary; Liu, Tong; Li, Guangping; Fu, Huaying (Frontiers in Cardiovascular Medicine, 2022)
Introduction: The diagnosis of heart failure with preserved ejection fraction (HFpEF) remains challenging. In this study, a novel echocardiographic index based on three-dimensional and tissue Doppler echocardiography for diagnosing and estimating prognosis in HFpEF. Materials and Methods: Patients with symptoms and/or signs of heart failure and normal left ventricular ejection fraction (LVEF ≥50%) who underwent right heart catheterization were screened. Patients were divided based on pulmonary capillary wedge pressure (PCWP) of ≥15mmHg and PCWP < 15mmHg. A diagnosis of HFpEF was confirmed by PCWP of ≥15mmHg according to ESC guidelines. A novel index was calculated by the ratio between stroke volume standardized to body surface area (SVI) and tissue Doppler mitral annulus systolic peak velocity S’ (SVI/S’). Its diagnostic and prognostic values were determined. Results: A total of 104 patients (mean age 64 ±12 years) were included. Of these, 63 had PCWP ≥15mmHg and 41 patients had PCWP <15mmHg. Compared to the PCWP <15mmHg group, the ≥15mmHg group had a significantly lower SVI/S’ (P <0.001). Logistic regression showed that SVI/S’ was associated with high PCWP measured invasively. The SVI/S’ had an area under the curve of 0.761 for diagnosing classifying between PCWP ≥15mmHg and <15mmHg. Kaplan–Meier analysis showed that the lower SVI/S’ group showed a poorer prognosis. Conclusions: SVI/S’ is a non-invasive index calculated by three-dimensional and tissue Doppler echocardiography. It is a surrogate measure of PCWP and can be used to diagnose and determine prognosis in HFpEF.